Modelo de apoio ao estudo de pacientes em oncologia pediátrica utilizando raciocínio baseado em casos e mineração de dados - Cruz, Jailton Cardoso da (2014)
This work aims to propose a recommendation model of prescription items for Pediatric Oncology based on data extraction from Electronic Patient Record. These data are used as indexed cases to aid providers of medical service based on the similarity of prescriptions, according to the patient's history. From the viewpoint of aid medical education, the modeling objective support the student or health professional in understanding the decision-making process during the prescription items oncological medical treatment, for example drugs, laboratory exams or images exams, diet, gases, care, chemotherapy, radiotherapy. To develop the model, was used the approach of Case Based Reasoning (CBR), through the representation of prescription medical base-case, indexed by their treatment items. During the recovery phase of cases, we used the tool. Data Mining by applying the model of association rule, together with the algorithm "apriori" for obtaining the similarity between cases. To update the case base, a procedure database for performing the process of Extraction, Transformation and Load of the database was developed. The developed model was applied in the database of the Electronic Patient Record of the Santa Casa de Misericordia de Maceio, based on Hospital Management Systems "MV Sistemas", deployed in the unit since 2005. For the presentation of results, was used the Oracle Data Miner tool, which allowed access to the database and analysis of selected cases by identifying key words contained in the evolution of the clinical condition of the patient. The application of the experiments validate the occurrence of allowed combined application of items of treatment according to the keywords, which can be used as input in the process of making medical decision and tutoring.